Significance of Milk pH in Newborn Infants. Issue 5839 (2nd December 1972) - Harrison, V. C.; Peat, G.
Abstract : Bottle-fed infants do not gain weight as rapidly as breast-fed babies during the first week of life. This weight lag can be corrected by the addition of a small amount of alkali (sodium bicarbonate or trometamol) to the feeds. The alkali corrects the acidity of cow's milk which now assumes some of the properties of human breast milk. It has a bacteriostatic effect on specific Escherichia coli in vitro, and in infants it produces a stool with a preponderance of lactobacilli over E. coli organisms. When alkali is removed from the milk there is a decrease in the weight of an infant and the stools contain excessive numbers of E. coli bacteria. A pH-corrected milk appears to be more physiological than unaltered cow's milk and may provide some protection against gastroenteritis in early life. Its bacteriostatic effect on specific E. coli may be of practical significance in feed preparations where terminal sterilization and refrigeration are not available. The study was conducted during the week after birth, and no conclusions are derived for older infants. The long-term effects of trometamol are unknown. No recommendation can be given for the addition of sodium bicarbonate to milks containing a higher content of sodium.